USO DO MATERIAL CONCRETO: UM FATOR FACILITADOR DA ENSINAGEM DE FRAÇÕES COM ALUNOS DE 5ª SÉRIE - Santos, Paulo Cesar Alves dos (2010)
The concept of fractionary number is sufficiently complex of the mathematical point of view and generates, therefore, a series of difficulties in the process of ensinagem in basic education. The present dissertação if considered to answer the following question of research: Which the possible contributions of the material concrete, ally to the methodology of resolution of problems, for the ensinagem of fractions the pupils of fifth series? The norteador objective was to investigate the strategies that the pupils of 5ª series of Basic Ensino, use front the problems that approach the fraction concept, according to theoretical classification proposal for Nunes et al. (2003). For in such a way, a disgnostic study in one was become fullfilled 5ª series of Basic Ensino, with 28 pupils, of which the strategies of 10 pupils had been analyzed, forming two groups. In the gotten results one evidenced that it did not have an equitable performance enters the five meanings of the fraction, in the direction of that it had a bigger difficulty in the meanings part-all, quotient and minors in number, measure and operator. How much to the strategies of resolution of the problems he did not have a regularity, therefore, the pupils had demonstrated to variations in the resolution of one same situation problem. In other words, for one exactly meant we find different strategies of resolution. All the used strategies had been of great value in the ensinagem process, however we detach those that had been used the material concrete for the development of the reasoning of the pupil. These results lead to conclude that the boarding that if makes of the fraction concept and its meanings, does not guarantee that the pupil constructs the knowledge of this same concept using the material concrete. However, we detach the biggest interatividade of concepts and problems of the pupils with the situations problems that were offered to them. Making with this an interchange between teaching and apprehending ( ensinagem ).